A Performance Study of Wireless Broadband Access (WiMAX) - Al-Adwany, Maan A. S. (Iraqi Journal for Electrical and Electronic Engineering, 2011)
WiMAX (worldwide interoperability for microwave access) is one of the wireless broadband access technologies which supplies broadband services to clients, but it surpasses other technologies by its coverage area, where one base station can cover a small city. In this paper, WiMAX technology is studied by exploring its basic concepts, applications, and advantages / disadvantages. Also a MATLAB simulator is used to verify the operation of the WiMAX system under various channel impairments and for variety of modulation schemes. From the simulation results, we found that WiMAX system works well in both AWGN and multipath fading channels, but under certain constraints that are addressed in this paper.